Microscopic Studies of Various Sizes of Gold Nanoparticles and Their Cellular Localizations. (28th July 2013) - Boyoglu, Cemil; He, Qingwen; Willing, Gerold; Boyoglu-Barnum, Seyhan; Dennis, Vida A.; Pillai, Shreekumar; Singh, Shree R.
Abstract : Gold nanoparticles (GNPs) are widely used in biological and clinical applications due to their favorable chemical and optical properties. GNPs can be used for drug delivery to targeted cells. In addition, GNPs serve as ideal probes for biological and cell imaging applications. Recent studies indicate that the size diversity of GNPs plays an important role in targeting cellular components for biomedical applications. In this study, we conducted a series of studies using different sizes of gold nanoparticles, including 3, 10, 25, and 50 nm, to determine the effect of size variations on their intracellular localizations. Our cytotoxicity studies of GNPs into the HEp-2 cells using MTT assay indicated that 3 nm GNPs possess the highest toxicity. We exposed HEp-2 cells with various sizes of gold nanoparticles for different time intervals (1, 2, 4, 12, and 24 h) followed by imaging using scanning electron microscope (SEM) and atomic force microscope (AFM). Our SEM and AFM results showed that, after 1 hr incubation, 3 and 10 nm gold nanoparticles entered the nucleus, whereas 25 and 50 nm particles accumulated around the nucleus. As the time of exposure increased, GNPs entered the cells and accumulated in the cytosol and nucleus based solely on their sizes.